Molecular diversity of babycorn (Zea mays) inbred lines by rice SSR Marker - Rani, Jyoti; Rashmi, Kumari; Sinha, Sweta; Sahay, Sanjay; Mandal, S S; Singh, Birender (The Indian Journal of Agricultural Sciences, 2020)
A set of 24 maize inbred lines were analysed by using Rice SSR markers (40). Out of which, 14 SSR markers were found to be amplified and reproducible in which 10 markers showed polymorphism and rest showed monomorphic bands. A total of 32 polymorphic alleles were found. The average polymorphic information content (PIC) value was 0.28 with maximum 0.36 (RM552) and minimum 0.14 (RM216). By the use of Unweighted paired group method (UPGMA) for cluster analysis and formed four clusters in which genotype CML425 was found extremely diverse from rest of the genotypes. This represents its unique genetic structure from the rest genotypes. The overall result indicates that the genotypes present in these clusters have maximum genetic diversity that will help in classifying various genotypes in exact heterotic groups for future breeding programme. The study provided sufficient information about the genetic diversity of maize inbreds and that also identified common markers for rice and maize genetic studies that can be helpful for reducing cost effective measures for producing crop specific markers. In this way, identified clusters may be used for future breeding programme. This study also concluded that SSR marker can be taken as good complementing tool.